An automated standard-based life cycle quality inspection methodology for smart precast concrete solutions in buildings. Issue 3 (3rd July 2019) - Hajdukiewicz, Magdalena; Goggins, Jamie; de la Torre, Oscar; Holleran, Dave; Keane, Marcus M.
ABSTRACT: Built2Spec research project brought together a new and breakthrough set of tools in order to improve construction quality inspection processes. These can be put into the hands of construction stakeholders to help meet Europe's energy efficiency targets, standards for constructing and retrofitting buildings, and related policy ambitions. This paper focuses on the automated standard-based life cycle quality inspections for precast concrete structural building elements that can be enhanced by leveraging a range of different technologies. Particular attention is placed on the use of embedded sensors in the precast concrete structural building elements as a tool to support quality assurance of these elements. Starting with the design, through manufacturing, delivery to site, installation, commissioning and operation until the end of life, the performance of precast concrete building elements is monitored and controlled to ensure their compliance with specifications, standards and guidelines. The outputs of proposed technologies integrated within the virtual construction management platform (VCMP) can enable automated continuous quality checks, while making them accessible to stakeholders through the life of a building. The measurements to support the development of this methodology were provided by a newly constructed demonstration building in Ireland.